Comparison of the clinical and biochemical profile of metabolic syndrome between obese children below and above 10 years attending paediatric clinic HUSM from 2006-2016 - Men, Khoo Kay (2016)
INTRODUCTION The burgeoning childhood obesity epidemic predisposes increasing numbers of children to the biochemical derangements that constitute metabolic syndrome, a cluster of metabolic risk factors that if unchecked can progress towards the development of cardiovascular disease and diabetes with their attendant morbidity and mortality in adulthood. Previous studies in children had reported varying rates of prevalence due to a lack of a universally accepted definition for paediatric metabolic syndrome. OBJECTIVE To determine if there is a significantly different clinical and biochemical profile of metabolic syndrome between obese children below and above 10 years attending Paediatric Clinic HUSM from 2006-2015 METHODS The medical records of 84 obese children under 18 years of age who were followed up at Paediatric clinic HUSM from 2006 to 2015 were identified and had their demographic (age, gender, ethnicity), anthropometric, (weight and height), clinical (BMI, systolic and diastolic blood pressure) and biochemical (serum triglyceride, total cholesterol, HDL-cholesterol, LDL- cholesterol, fasting blood sugar) parameters recorded, analysed and compared. RESULTS The majority of subjects in both age groups were boys, 68.2% of those less than 10 years and 62.8% in those above 10 years. Mean age of subjects was 9.69 years. An almost equal number of children had been brought to medical attention for obesity (41 vs 43) and fulfil the IDF criteria for metabolic syndrome (11 vs 12) in both groups. As expected, the mean body mass index, waist circumference, systolic blood pressure, and serum triglyceride levels are significantly higher in children >10 years of age. There were no significant differences in birth weight, diastolic blood pressure, total cholesterol, HDL cholesterol, LDL cholesterol or fasting plasma glucose levels between the 2 groups. CONCLUSION The data obtained during this study demonstrates a high prevalence rate (31%) of metabolic syndrome among obese children attending paediatric clinic in HUSM, which is comparable to findings from other studies in developed countries. In view of the alarming presence of components of metabolic syndrome even in children less than 10 years of age, efforts aimed at the prevention of childhood obesity in the community should be stepped up.